2012
DOI: 10.1002/jbmr.1582
|View full text |Cite|
|
Sign up to set email alerts
|

Does osteoporosis therapy invalidate FRAX for fracture prediction?

Abstract: Ten-year fracture risk assessment with the fracture risk assessment system (FRAX) is increasingly used to guide treatment decisions. Osteoporosis pharmacotherapy reduces fracture risk, but the effect is greater than can be explained from the increase in bone mineral density (BMD). Whether this invalidates fracture predictions with FRAX is uncertain. A total of 35,764 women (age !50 years) and baseline BMD testing (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007) had FRAX probabilities re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(62 citation statements)
references
References 44 publications
2
59
0
1
Order By: Relevance
“…In those receiving treatment for osteoporosis, FRAX is likely to overestimate fracture probability since treatment effects are not accommodated in the model. The empirical data suggest that FRAX remains a good predictive tool in women currently or previously on treatments for osteoporosis [88], possibly related to the contribution of treatment-induced changes in BMD.…”
Section: Concurrent Treatmentmentioning
confidence: 99%
“…In those receiving treatment for osteoporosis, FRAX is likely to overestimate fracture probability since treatment effects are not accommodated in the model. The empirical data suggest that FRAX remains a good predictive tool in women currently or previously on treatments for osteoporosis [88], possibly related to the contribution of treatment-induced changes in BMD.…”
Section: Concurrent Treatmentmentioning
confidence: 99%
“…(21) Observational studies have found that the FRAX is not sensitive enough to the changes in BMD and fracture risk with treatment, with fracture probabilities tending to increase because of increasing age during treatment. (22,23) In addition, FRAX fracture risk calculations do not take into account how recently a fracture occurred. Recent clinical trial and observational data in individuals treated for osteoporosis suggest that a history of recent fracture during treatment is associated with an increased risk of another fracture during treatment.…”
Section: Fracture Risk As a Goalmentioning
confidence: 99%
“…Several treatments have had efficacy evaluated in terms of FRAX score at baseline [69][70][71][72][73], indicating either a greater anti-fracture efficacy at higher risk or no interaction between anti-fracture efficacy and baseline risk. In a single study, FRAX has been shown to perform similarly in treated and untreated patients, suggesting that the impact of treatment on fracture risk may be difficult to detect and that FRAX may have a low sensitivity for treatment-induced reductions in fracture risk [74]. A recent analysis of a subset of the same cohort, comprising more than 11,000 women undergoing baseline and follow-up DXA scans, not only confirmed that FRAX scores were strongly predictive of incident major fracture and hip fracture over 4 years of treatment but also reported that the change in FRAX score on treatment was not independently associated with the subsequent risk of a major fracture (P=0.8) or hip fracture (P=0.3) [75].…”
Section: Frax Probabilitymentioning
confidence: 99%